Enhancing the Competencies of Islamic Religious Counselors through Creative Digital Content Design Training on Religious Moderation in Banjarnegara Regency - Nurus Sarifatul Ngaeni; Mukhlish Mukhlish; Tri Haryanti; Muh. Zia Ulkhaq (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2026)
The rapid expansion of digital communication has transformed the way religious messages are disseminated, requiring Islamic religious counselors to develop competencies in producing engaging digital content. However, many counselors in Banjarnegara Regency still have limited technical skills in graphic design, reducing the effectiveness of communicating religious moderation through social media. This community engagement program aimed to enhance the digital content design competencies of 161 Islamic religious counselors at the Ministry of Religious Affairs Office of Banjarnegara Regency by integrating graphic design training with religious moderation principles. A participatory training approach was employed, combining lectures, demonstrations, hands-on practice, mentoring, and performance evaluation. Participants' competencies were assessed using pre-test and post-test instruments, and the data were analyzed through descriptive statistics and a paired-samples t-test to determine the significance of learning outcomes. The findings revealed a substantial improvement in participants' competencies, with the mean score increasing from 55.52 in the pre-test to 85.29 in the post-test (p < 0.001). Participants also demonstrated improved abilities to develop visually appealing, informative, and persuasive digital content that effectively conveyed the values of religious moderation. These findings suggest that integrating graphic design training with digital literacy and religious moderation education provides an effective strategy for strengthening the digital communication competencies of Islamic religious counselors. The program contributes to the broader digital transformation of religious outreach and offers a replicable model for enhancing community-based religious communication in the digital era.